GENDER ASPECT IN THE SPEECH ACT: GENDER ASPECT IN THE SPEECH ACT - Atamuratova, Manzura (Журнал иностранных языков и лингвистики, 2025)
"Gender characteristics of communicators determine the properties of the communicative act, its verbal and non-verbal components, along with the conditions of development of the communication situation, the propositional content and illocutionary force of the utterance